Procedures Used in Managing SARS-CoV-2 Infected Dental Personnel or Patients: A Case Study From a Thai Dental Hospital - Pittayapat, Pisha; Ampornaramveth, Ruchanee; Jirachoksopon, Chongpean; Suvarnbriksha, Kanchana; Kattapong, Siripun; Pethprasert, Theerabhorn; Kungsadalpipob, Kajorn; Chantarangsu, Soranun; Thanyasrisung, Panida; Koottathape, Natthavoot; Tamsailom, Suphot; Linsuwanont, Pairoj; et al. (Frontiers in Oral Health, 2021)
SARS-CoV-2 can transmit undetected from asymptomatic and pre-symptomatic patients in dental clinics. Triaging dental patients using temperature and questionnaire screening cannot completely exclude asymptomatic SARS-CoV-2 infected individuals. Hence, asymptomatic SARS-CoV-2 infected individuals might visit dental hospitals/clinics seeking dental treatment without knowing that they are infected and might infect others, especially in a pandemic area. Ideally, a nasopharyngeal swab for real-time polymerase chain reaction or rapid antigen screening for dental personnel and patients prior to their appointment should be done. However, the implementation of this approach is impractical in some situations. Here, we describe the procedures for dental hospitals/clinics in case of an asymptomatic SARS-CoV-2 infected individual involved in dental service/treatment and later after testing positive for SARS-CoV-2. Potential closely contacted individuals were traced and classified according to their exposure risk. The recommended course of action is to identify individuals based on their risk and take the risk-appropriate action. We also discuss the implementation of these procedures in a dental setting during the COVID-19 pandemic in our school as a case study.